2004
DOI: 10.1111/j.1468-2982.2004.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Glutamate Levels in Chronic Migraine

Abstract: Both preclinical and clinical data link glutamate to the migraine pathophisiology. Altered plasma, platelets and cerebrospinal (CSF) glutamate levels have been reported in migraine patients. Chronic migraine is comorbid with several conditions. It has been recently shown chronic migraine comorbidity with fibromyalgia. The objective of this study was to study cerebrospinal fluid glutamate levels in chronic migraine patients with and without fibromyalgia. We studied 20 chronic migraine patients, with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
99
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 27 publications
8
99
0
5
Order By: Relevance
“…We have recently shown that chronic migraine is related to a hyperglutamatergic state in the brain, confirmed by higher cerebrospinal fluid glutamate levels in chronic migraineurs compared to controls [10]. Therefore, topiramate may be a candidate for chronic migraine prevention.…”
Section: Discussionmentioning
confidence: 95%
“…We have recently shown that chronic migraine is related to a hyperglutamatergic state in the brain, confirmed by higher cerebrospinal fluid glutamate levels in chronic migraineurs compared to controls [10]. Therefore, topiramate may be a candidate for chronic migraine prevention.…”
Section: Discussionmentioning
confidence: 95%
“…Cognitive functions involve both brain regions (cortical and subcortical areas) 14 and several neurotransmitters such as dopamine and noradrenaline, important in verbal fluency, attention, working memory, learning, motivation and adaptive behavior, and glutamate, which also seems to play an important role in learning and memory [22][23][24][25][26] . It is believed that these neurotransmitters play an important role in the pathophysiology of migraine [27][28][29][30] . Accordingly, maybe neurochemical aspects involved in the physiopathology of migraine and cognition mechanisms may explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily the latter is hypothesised to contribute to chronic sensitisation of central neurons (i.e. in the nucleus trigeminus) (19)(20)(21)(22). It is believed that this process also occurs in other chronic pain disorders such as fibromyalgia, where increased CSF concentrations of NGF, BDNF and glutamate have been found (21).…”
Section: Discussionmentioning
confidence: 99%